The Expression of PTHLH in Human Gastric Mucosa Enterochromaffin-Like Cells - Liu, Cuiping (Springer US, 2010)
BACKGROUND: Gastrectomy may disturb the body’s mineral homeostasis, with osteopenia and osteoporosis being among the late outcomes. Parathyroid hormone-like hormone (PTHLH) was detected in rat gastric enterochromaffin-like (ECL) cells in 2005, and some researchers suggested that it was the hypothetical hormone gastrocalcin that is believed to lead to osteoporosis. AIMS: Our objective was to learn whether PTHLH is expressed in human gastric ECL cells and to form a basic understanding about the relationship between PTHLH and gastrin. METHODS: We collected normal human gastric mucosa specimens and serum samples from 28 patients. RESULTS: RT-PCR and immunohistochemical analysis demonstrated weak expression of PTHLH in ECL cells at the RNA and protein levels. A low level of PTHLH expression was also found in the serum. Serum gastrin did have a significant positive correlation with the relative ratio of PTHLH mRNA to β-actin levels in gastric mucosa (r (s) = 0.569, p = 0.002). CONCLUSIONS: This indicates that PTHLH has a low signal expression in human gastric ECL cells and that serum gastrin levels correlate with PTHLH RNA levels in gastric mucosa. Further work is needed to evaluate the functional role of PTHLH in ECL cells and to determine whether PTHLH is gastrocalcin.